Responder
Here are the solutions to the quadratic equations:
1. **(9) \(4x^{2} - 4x - 3 = 0\):**
\(x = 1.5\) and \(x = -0.5\)
2. **(10) \(3x^{2} + 8x = -2\):**
\(x \approx -0.28\) and \(x \approx -2.39\)
3. **(11) \(-5x^{2} - 2x + 1 = 0\):**
\(x \approx 0.29\) and \(x \approx -0.69\)
4. **(12) \(-3x^{2} - 11x = 9\):**
\(x \approx -1.23\) and \(x \approx -2.43\)
5. **(13) \(3x^{2} + 33x + 30 = 0\):**
\(x = -1\) and \(x = -10\)
6. **(14) \(7 - 12x - x^{2} = 0\):**
\(x = -6 + \sqrt{43}\) and \(x = -6 - \sqrt{43}\)
7. **(15) \(16x + 12 - x^{2} = 0\):**
\(x \approx 16.72\) and \(x \approx -0.72\)
8. **(16) \(\frac{2}{3}x^{2} - \frac{5}{2}x + \frac{1}{4} = 0\):**
\(x = \dfrac{15 + \sqrt{201}}{8}\) and \(x = \dfrac{15 - \sqrt{201}}{8}\)
If you need further explanations or assistance with any of these solutions, feel free to ask!
Solución
Sure! Let's solve each of the quadratic equations from (9) to (16), providing solutions either rounded to two decimal places or in surd (exact radical) form as specified.
---
### **(9) \(4x^{2} - 4x - 3 = 0\)**
**Solution Method:** Quadratic Formula
\[
x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}
\]
Here, \(a = 4\), \(b = -4\), and \(c = -3\).
\[
x = \frac{4 \pm \sqrt{16 + 48}}{8} = \frac{4 \pm \sqrt{64}}{8} = \frac{4 \pm 8}{8}
\]
\[
\Rightarrow x = \frac{12}{8} = 1.5 \quad \text{and} \quad x = \frac{-4}{8} = -0.5
\]
**Solutions:**
\(x = 1.5\) and \(x = -0.5\)
---
### **(10) \(3x^{2} + 8x = -2\)**
**Rearranged Equation:** \(3x^{2} + 8x + 2 = 0\)
**Solution Method:** Quadratic Formula (Rounded to two decimal places)
\[
x = \frac{-8 \pm \sqrt{64 - 24}}{6} = \frac{-8 \pm \sqrt{40}}{6} = \frac{-8 \pm 6.3246}{6}
\]
\[
x_1 = \frac{-8 + 6.3246}{6} \approx -0.28 \quad \text{and} \quad x_2 = \frac{-8 - 6.3246}{6} \approx -2.39
\]
**Solutions:**
\(x \approx -0.28\) and \(x \approx -2.39\)
---
### **(11) \(-5x^{2} - 2x + 1 = 0\)**
**Rearranged Equation:** \(5x^{2} + 2x - 1 = 0\)
**Solution Method:** Quadratic Formula (Rounded to two decimal places)
\[
x = \frac{-2 \pm \sqrt{4 + 20}}{10} = \frac{-2 \pm \sqrt{24}}{10} = \frac{-2 \pm 4.899}{10}
\]
\[
x_1 = \frac{-2 + 4.899}{10} \approx 0.29 \quad \text{and} \quad x_2 = \frac{-2 - 4.899}{10} \approx -0.69
\]
**Solutions:**
\(x \approx 0.29\) and \(x \approx -0.69\)
---
### **(12) \(-3x^{2} - 11x = 9\)**
**Rearranged Equation:** \(-3x^{2} - 11x - 9 = 0\)
**Simplified Equation:** \(3x^{2} + 11x + 9 = 0\)
**Solution Method:** Quadratic Formula (Rounded to two decimal places)
\[
x = \frac{-11 \pm \sqrt{121 - 108}}{6} = \frac{-11 \pm \sqrt{13}}{6}
\]
\[
\sqrt{13} \approx 3.6056
\]
\[
x_1 = \frac{-11 + 3.6056}{6} \approx -1.23 \quad \text{and} \quad x_2 = \frac{-11 - 3.6056}{6} \approx -2.43
\]
**Solutions:**
\(x \approx -1.23\) and \(x \approx -2.43\)
---
### **(13) \(3x^{2} + 33x + 30 = 0\)**
**Solution Method:** Quadratic Formula
\[
x = \frac{-33 \pm \sqrt{1089 - 360}}{6} = \frac{-33 \pm \sqrt{729}}{6} = \frac{-33 \pm 27}{6}
\]
\[
x_1 = \frac{-33 + 27}{6} = \frac{-6}{6} = -1 \quad \text{and} \quad x_2 = \frac{-33 - 27}{6} = \frac{-60}{6} = -10
\]
**Solutions:**
\(x = -1\) and \(x = -10\)
---
### **(14) \(7 - 12x - x^{2} = 0\)**
**Rearranged Equation:** \(-x^{2} - 12x + 7 = 0\)
**Simplified Equation:** \(x^{2} + 12x - 7 = 0\)
**Solution Method:** Quadratic Formula (Expressed in Surd Form)
\[
x = \frac{-12 \pm \sqrt{144 + 28}}{2} = \frac{-12 \pm \sqrt{172}}{2} = \frac{-12 \pm 2\sqrt{43}}{2}
\]
\[
x = -6 \pm \sqrt{43}
\]
**Solutions:**
\(x = -6 + \sqrt{43}\) and \(x = -6 - \sqrt{43}\)
---
### **(15) \(16x + 12 - x^{2} = 0\)**
**Rearranged Equation:** \(-x^{2} + 16x + 12 = 0\)
**Simplified Equation:** \(x^{2} - 16x - 12 = 0\)
**Solution Method:** Quadratic Formula (Rounded to two decimal places)
\[
x = \frac{16 \pm \sqrt{256 + 48}}{2} = \frac{16 \pm \sqrt{304}}{2} \approx \frac{16 \pm 17.4356}{2}
\]
\[
x_1 = \frac{16 + 17.4356}{2} \approx 16.72 \quad \text{and} \quad x_2 = \frac{16 - 17.4356}{2} \approx -0.72
\]
**Solutions:**
\(x \approx 16.72\) and \(x \approx -0.72\)
---
### **(16) \(\frac{2}{3}x^{2} - \frac{5}{2}x + \frac{1}{4} = 0\)**
**Solution Method:** Quadratic Formula (Expressed in Surd Form)
First, eliminate fractions by multiplying the entire equation by 12:
\[
12 \cdot \left(\frac{2}{3}x^{2} - \frac{5}{2}x + \frac{1}{4}\right) = 0 \Rightarrow 8x^{2} - 30x + 3 = 0
\]
Now, apply the quadratic formula:
\[
x = \frac{30 \pm \sqrt{900 - 96}}{16} = \frac{30 \pm \sqrt{804}}{16} = \frac{30 \pm 2\sqrt{201}}{16} = \frac{15 \pm \sqrt{201}}{8}
\]
**Solutions:**
\(x = \dfrac{15 + \sqrt{201}}{8}\) and \(x = \dfrac{15 - \sqrt{201}}{8}\)
---
Feel free to ask if you need further explanations or assistance with any of these solutions!
Revisado y aprobado por el equipo de tutoría de UpStudy
Explicar
Simplifique esta solución